Perancangan Sistem Informasi Website Sewa Kos (E-Kos) Studi Kasus Surabaya - Fitriah Fitriah; Tining Haryanti (FORTEI Regional VII Jawa Timur, 2022)
Surabaya is one of the largest cities in Indonesia, so it is the main attraction for most people to be able to live or try their luck there, many people come from various regions to work or continue their education. With so many immigrants, the need for a place to live is also increasing, but here there are obstacles, namely the difficulty of getting information about where to live, so that in this study an information system was designed, namely a website-based E-boarding application as a means of providing information about boarding houses that is effective so that it makes it easier for housing seekers, as well as boarding managers, can be used for promotional media for the boarding house that they will rent out and manage everything about the boarding house quickly and easily. The waterfall method is used in the development of this system, modeling using UML (Unified Modeling Language). PHP is the programming language used in making this application with the XAMPP webserver. This e-kos is equipped with a feature for booking boarding rooms and boarding payments without having to come directly to the location and making it easier for renters and boarding owners.